Propuesta de un sistema de gestión ambiental basado en la NTC ISO 14001:2015 en una empresa de tratamiento de agua potable (2021)
The continuous search for opportunities for improvement in companies to achieve quality and recognition standards during the preparation or provision of their products or services, has led many companies to implement management systems, such as the environmental management system (EMS), the which allows avoiding the increase in environmental concerns as a consequence of an increase in the probability of negative impact on the environment, through compliance with the requirements stipulated in standards such as ISO 14001. Therefore, the main objective of this degree project It consisted of the proposal of an environmental management system that would allow adequate compliance with the NTC ISO 14001: 2015 standard in the treatment of PTAP drinking water in a public service company in the municipality of the province of Sabana Centro in the department of Cundinamarca.